An Investigation of Teacher Evaluation Practice in Indiana: PL 90 Implementation and Issues for Administrators. Issue 1 (January 2019) - Harvey, Michael W.; Boyland, Lori G.; Quick, Marilynn M.
This study investigated teacher evaluation practices used in Indiana as the state was implementing a mandated teacher evaluation system (Public Law 90) and early reporting of subsequent teacher effectiveness results by the Indiana Department of Education. The study surveyed public school administrators: (a) superintendents, (b) special education directors, and (c) K-12 building principals via e-mail using Qualtrics. A total of 2, 444 administrators were invited to participate with a 28% return rate. Summative and formative teacher evaluation methods were used, but emergent methods (as mandated in PL 90) were not widely used. Recommendations for a more unified approach to teacher evaluation are emphasized.